2007
DOI: 10.1159/000110446
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-O-Gallate Inhibits the Angiotensin II-Induced Adhesion Molecule Expression in Human Umbilical Vein Endothelial Cell Via Inhibition of MAPK Pathways

Abstract: Epigallocatechin-3-O-gallate (EGCG) is the main catechin, which is derived from Camellia sinensis plant. Vascular cell adhesion molecules (VCAMs) and intercellular adhesion molecules (ICAMs) mediate the binding of inflammatory cells onto the vascular wall-promoting the early phase of atherosclerosis. In the present study, we investigated the mechanism(s) by which EGCG inhibits angiotensin II (Ang II)-induced elevation of the membrane associated VCAM-1 and ICAM-1 in human umbilical vein endothelial cells (HUVEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…We recently reported that EGCG and ECG treatment inhibited p38 MAPK activation in oncostatin M-stimulated HGFs [22]. Moreover, Chae et al reported that EGCG suppressed ERK phosphorylation in angiotensin 2-treated human umbilical vein endothelial cells [23]. Bigelow et al also reported that EGCG and ECG suppressed ERK activation in hepatocyte growth factor-treated tumorigenic breast epithelial cells [24].…”
Section: Discussionmentioning
confidence: 96%
“…We recently reported that EGCG and ECG treatment inhibited p38 MAPK activation in oncostatin M-stimulated HGFs [22]. Moreover, Chae et al reported that EGCG suppressed ERK phosphorylation in angiotensin 2-treated human umbilical vein endothelial cells [23]. Bigelow et al also reported that EGCG and ECG suppressed ERK activation in hepatocyte growth factor-treated tumorigenic breast epithelial cells [24].…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, treatment with luteolin was found to inhibit the p38 and ERK1/2 phosphorylation induced by TNF-α. Moreover, the activation of p38 and ERK1/2 has been shown to be associated with the VCAM-1, ICAM-1 and Bcl-2 expression [38][39][40] . This finding was confirmed by our observation that the above three TNF-induced protein expression levels were partly abolished by the inhibitors of p38 and/or ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…First, reduced pathological cells in the periphery are assumed to reduce the frequency of these cells coming across the CNS. Second, EGCG reduces the production or expression of the molecules known to facilitate leukocyte transendothelial migration, such as chemokines IL-8 and monocyte chemoattractant protein-1 [45][46][47] and adhesion molecules 48,49 and to inhibit migration of neutrophils, 50,51 CD8 ϩ T cells, 49 and B cells. 52 Third, the observed EGCG-induced reduction in IFN-␥ and IL-17 production and the proportion of IL-17-IFN-␥ double-positive CD4 ϩ T cells may contribute to the reduced leukocyte infiltration because, as reported, IFN-␥ facilitates Th17 migration across the BBB by enhancing endothelial expression of adhesion molecule ICAM-1, and IL-17 is capable of disrupting the BBB; IL-17-IFN-␥ double-positive cells have a higher capacity for crossing the BBB than either singlepositive cells.…”
Section: Discussionmentioning
confidence: 99%